Dampak Penetapan Tarif Ekspor Impor Amerika Serikat dan China 6 Juli 2018 Terhadap Kemakmuran Pemegang Saham dan Likuiditas Saham Pada Indeks LQ45 - admin, Herry Giovandi B1021161033 (Jurnal Manajemen Update, 2021)
ABSTRACTThe United States-China trade war is a big trade war especially about productâ€™s import tariff from each country started from 2017 and the peak of this trade war is happened when US decide 25% tariff to China on 6 July 2018 and then China apply the same tariff to US.This study aims to know about how is the influence of this export import tariff event to the wealth of the shareholders ( using abnormal return variable ) and stockâ€™s liquidity ( using trading volume activity variable ) in Indonesia especially for stocks which is registered in LQ45. The method to analysis data in this study is descriptive statistic, normality test and paired sample t-test if data distribution is normal and Wilcoxon signed rank test if data distribution is not normal. This studyâ€™s result shows the event of export import tariff between US and China 6 July 2018 didnâ€™t show any significant difference as we can see from theÂ  level of the significancy is above 0,05 at average abnormal return and average trading volume activity in financial sector, non financial sector or both of the sectors. This means not every events contain information that affect the decision of investor in investing.Â DAFTAR PUSTAKAAmadeo, Kimberly. 2020. Trade Wars and their Effect on the Economy and You. https://www.thebalance.com/trade-wars-definition-how-it-affects-you-4159973. (diakses 25 Januari 2021)Apridar. 2009. Ekonomi Internasional : Sejarah, Teori, Konsep dan Permasalahan dalam Aplikasinya. Yogyakarta: Graha Ilmu.Baker, H.K, dan G.E. Powell. 1993. â€œFurther evidence on managerial motives for stock splits. Quarterly Journal of Business and Economics. Vol. 32 : 20-30.BBCIndonesia. 2018. AS-Cina Perang Dagang, Indonesia Tetap Terpengaruh. https://www.bbc.com/indonesia/indonesia-43620873. (diakses 25 Januari 2021)Brigham, Eugene F. dan Louis C. Gapenski. 1996. Intermediate Financial Management. Florida : The Dyden Press.Â Chen, G., Firth, M. dan Rui, O. M. 2001. â€œThe Dynamic Relation Between Stock Return Trading Volume and Volatilityâ€. The Financial Review. 36(3). pp.153-174Chordia, Tarun dan Bhaskaran, Swamintahan. 2000. â€œTrading Volume and Cross Autocorrelations in Stock Returnsâ€. The Journal of Finance. Vol LV, No.2 (April 2000), pp. 913-935Djohanputro, Bramantyo. 2008. Manajemen Risiko Korporat. Jakarta: Penerbit PPM.Fama, E.S. 1970. â€œEfficient Capital Markets : A Review of Theory and Empirical Workâ€. Journal of Finance. Vol 25, p.383-417Ghozali, Imam. 2013. Aplikasi Analisis Multivariate dengan Program IBM SPSS 21.Edisi Ketujuh. Badan Penerbit Universitas Diponegoro. Semarang.Hartono, Jogiyanto. 2008. Metodelogi Penelitian Sistem Informasi. Yogyakarta: CV Andi Offset.Hartono, Jogiyanto. 2010. Studi Peristiwa: Menguji Reaksi Pasar Modal Akibat Suatu Peristiwa. Yogyakarta: BPFE Yogyakarta.Hartono, Jogiyanto. 2014. Teori Portofolio dan Analisis Investasi. Yogyakarta: BPFE Yogyakarta.Hasnawati, S. 2005. â€œImplikasi Keputusan Investasi, Pendanaan, dan Dividen Terhadap Nilai Perusahaan Publik di Bursa Efek Jakartaâ€. Usahawan : No.06/Th XXIX. September 2005 :33-41.Hidayat, Khomarul. 2018. Inilah Perjalanan Waktu Perang Dagang Amerika Serikat Versus China. https://investasi.kontan.co.id/news/inilah-perjalanan-waktu-perang-dagang-amerika-serikat-versus-china.html.Â  (diakses 6 Juni 2020).Infojabodetabek. 2018. Daftar Saham Indeks LQ45 (Februari 2018 â€“ Juli 2018). https://www.infojabodetabek.com/daftar-saham-indeks-lq45-februari-2018-juli-2018.html. (diakses tanggal 6 Juni 2020)Junaedi, Dedi. 2005. â€œDampak Tingkat Pengungkapan Informasi Perusahaan Terhadap Volume Perdagangan dan Return Saham : Penelitian Empiris Terhadap Perushaan-Perushaan yang Tercatat di Bursa Efek Indonesiaâ€. Jurnal Akuntansi dan Keuangan Indonesia. Juli-Desember 2005, Vol 2, No. 2,pp. 1-28.Jogiyanto. 2010. Teori Portofolio dan Analisis Investasi. Yogyakarta: BPFE.Karpoff, Jonathan M. 1986. â€œA Theory of Trading Volumeâ€. The Journal of Finance. Vol. 41, No. 5 (December 1986), pp. 1069-1087.Krisharianto, Josef dan Djoni Hartono. 2007. â€œKajian Hubungan Antara Pertumbuhan Ekonomi, Perdagangan Internasional dan Foreign Direct Investmentâ€. Makalah disajikan dalam Parallel Session IIID : Trade (Growth & FDI), Departemen Perdagangan, Kampus UI Depok.Ksei. 2018. Pengumuman Corporate Action https://www.ksei.co.id/publications/corporate-action-schedules/masr. (diakses 6 Juni 2020).MacKinlay, A Craig. 1997. â€œEvent Studies in Economics and Finance.â€Journal of Economic Literature. Vol XXXV (March 1997), pp. 13-39Malini, Helma. 2019. "Efficient market hypothesis and market anomalies of LQ 45 index in Indonesia stock exchange." Sriwijaya International Journal of Dynamic Economics and Business 3.2 (2019): 107-121.Nor Hadi. 2013. Pasar Modal : Acuan Teoritis dan Praktis Investasi Keuangan Pasar Modal. Yogyakarta: Graha Ilmu.Pablo, Samuel. 2018. Kebijakan AS vs China yang Menyulut Perang Dagang di Dunia.https://www.cnbcindonesia.com/news/20180918115050-4-33623/kebijakan-as-vs-china-yang-menyulut-perang-dagang-di-dunia.html. (diakses 6 Juni 2020).Rodoni, Ahmad dan Yong, Othman. 2002. Analisis Investasi & Teori Portofolio.Jakarta: Raja Grafindo Persada.Setyawasih, Rianti. 2007. â€œStudy Tentang Peristiwa (Event Study) : Suatu Panduan Riset Manajemen Keuangan di Pasar Modalâ€. Jurnal Optimal. Vol. 1, No.1 (Maret 2007), Hal. 52-58.Santoso, Singgih. 2014. Statstik Parametrik Edisi Revisi. Jakarta : Elex Media KomputindoSicca, Shintaloka Pradita. 2018. Yang Perlu Dilakukan Indonesia dalam Perang Dagang AS- Cina. https://tirto.id/yang-perlu-dilakukan-indonesia-dalam-perang-dagang-as-cina-cNQT. (diakses 25 Januari 2021)Sugiyono. 2015. Metode Penelitian Kuantitaif, Kualitatif dan R&D. Bandung: CV.Alfabeta.Sukirno, Sadono.2005. Ekonomi Pembangunan, Proses, Masalah dan Dasar Kebijaksanaan, LPFEUI Jakarta.Sunariyah. 2011. Pengantar Pengetahuan Pasar Modal. Yogyakarta: UPP AMP YKPN.Suwardjono. 2008. Teori Akuntansi: Perekayasaan Laporan Keuangan (Edisi Ketiga). Yogyakarta: BPFE.Tandeilin, Eduardus. 2010. Portofolio dan Investasi Teori dan Aplikasi. Yogyakarta : Kanisius.Tribunmanado. 2019. Kronologi Lengkap Perang Dagang AS vs China, Sudah 30 Kali Sejak 2016. https://manado.tribunnews.com/2019/08/24/kronologi-lengkap-perang-dagang-as-vs-china-sudah-30-kali-sejak-2016?page=all.html. (diakses 6 Juni 2020).